Callus Induction of Piper betle L. Var Nigra Using 2,4-Dichlorofenoxyacetic Acidand 6-Benzil Aminopurin - Junairiah Junairiah; Purnomo Purnomo; Edy Setiti Wida Utami; Lilis Sulistyorini; Ni’matuzahroh Ni’matuzahroh (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Piper betle L var Nigra (black betel) is a member of Piperaceae family which has potential as medicinal plant due to its secondary metabolites. Callus culture is one of the alternative methods to elevate production of secondary metabolites. This study was aimed to determine the effect of 2,4-dichlorophenoxyacetic acid (2,4-D) and 6-benzil aminopurine (BAP) towards callus induction and growth, also to determine the most optimal variation of 2,4-D and BAP concentration for callus induction of black betel leaf explant. This study was a laboratory experimental study with complete randomized design. Black betel leaf explant was planted in Murashige and Skoog (MS) medium supplemented with 2,4-D and BAP growth regulators at concentration of 0.0 mg/L, 0.5 mg/L, 1.0 mg/L, 1.5 mg/L, 2.0 mg/L respectively. Parameter recorded for callus induction and growth including callus induction time (days), percentage of explant forming callus, fresh weight, dry weight, color and texture. After callus planted for 8 weeks, analysis was performed statistically. Result showed that 2,4-D and BAP supplementation to medium affected the growth of black bete l leaf explants. Additional concentration of 0.5 mg/L 2,4-D and 1.0 mg/L BAP growth regulators showed the fastest response in callus formation, at 7.25 days. Growth regulators of 2,4-D 0.5 mg/L and BAP 2.0 mg/L concentration produced the highest fresh and dry weight, at 0.6802 g and 0.0670 g respectively. The best treatment was used as a basis to produce secondary metabolites.